Digital Learning Experience: Pengembangan Mobile Learning Management System dengan Pendekatan RAD - Rinel, Ovel; Muchlis, Lita Sari; ., Zikrawahyu; Rahmi, Lidya; ., Adriyendi (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
Mobile learning design is a learning system that utilizes information technology integrated with academic administration, allowing students to access learning materials flexibly. This research aims to develop a Mobile Learning Management System (MLMS) system to help students of the Informatics Management Study Program, especially in the Algorithms and Data Structures course in managing administration, materials, and teaching activities online. This research uses the Rapid Application Development (RAD) method which consists of 4 stages, namely the requirements planning phase, user design phase, construction phase and cutover phase. This research produced a mobile learning application product validated using the Computer System Usability Questionnaire (CSUQ) instrument with an average score of 81.12% which is included in the very feasible category. This application provides administrative solutions so that learning media can be implemented in an integrated manner and can be used anytime and anywhere online.